Successful technological integration for competitive advantage in retail settings - Pantano, Eleonora, 1982- (Hershey, PA : Business Science Reference, An Imprint of IGI Global, 2015)
'This book examines the various effects of changing markets and subsequently how these changes cause retailers to meet consumer demand by integrating more sophisticated, advanced innovations in their daily practices'--
Includes bibliographical references (pages 340-394) and index.
Keywords: Retail trade -- Technological innovations; Retail trade -- Management